Ang2-Targeted Combination Therapy for Cancer Treatment - Liu, Na; Liu, Mengfang; Fu, Shengqiao; Wang, Jinglei; Tang, Haowen; Isah, Adamu Danbala; Chen, Deyu; Wang, Xu (Frontiers in Immunology, 2022)
Angiopoietin-2 (Ang2), a member of angiopoietin family, is widely involved in the process of vascular physiology, bone physiology, adipose tissue physiology and the occurrence and development of inflammation, cardiac hypertrophy, rheumatoid, tumor and other diseases under pathological conditions. The proliferation and metastasis of cancer largely depend on angiogenesis. Therefore, anti-angiogenesis has become the target of tumor therapy. Due to the Ang2 plays a key role in promoting angiogenesis and stability in vascular physiology, the imbalance of its expression is an important condition for the occurrence and development of cancer. It has been proved that blocking Ang2 can inhibit the growth, invasion and metastasis of cancer cells. In recent years, research has been constantly supplemented. We focuses on the mechanisms that regulate the expression of Ang2 mRNA and protein levels in different cancers, contributing to a better understanding of how Ang2 exerts different effects in different cancers and stages, as well as facilitating more specific targeting of relevant molecules in cancer therapy. At the same time, the importance of Ang2 in cancer growth, metastasis, prognosis and combination therapy is pointed out. Finally, we discuss the current investigations and future challenges of combining Ang2 inhibition with chemotherapy, immunotherapy, and radiotherapy to increase the efficacy of cancer patients. This review provides a theoretical reference for the development of new targets and effective combination therapy strategies for cancer treatment in the future.